2013
DOI: 10.2298/hemind121026009m
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the kinetics of essential oil hydrodistillation from plant materials

Abstract: The present work deals with the modeling of the kinetics of essential oils extraction from plant materials by water and steam distillation. The experimental data were obtained by studying the hydrodistillation kinetics of essential oil from juniper berries. The literature data on the kinetics of essential oils hydrodistillation from different plant materials were also included into the modeling. A physical model based on simultaneous washing and diffusion of essential oil from plant materials were developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 39 publications
2
24
0
3
Order By: Relevance
“…During the t ind , the EO volatile compounds begin to be released into the extraction media from exogenous secreting glands, according to the washing and diffusion model (Milojevic et al, 2013) but without actually separating. Since the temperature is continuously increased, an increase in pressure then follows within the exogenous glands (due to the expansion of the volatile compounds), leading to the cellular wall breakage and the release of the essential oil.…”
Section: Resultsmentioning
confidence: 99%
“…During the t ind , the EO volatile compounds begin to be released into the extraction media from exogenous secreting glands, according to the washing and diffusion model (Milojevic et al, 2013) but without actually separating. Since the temperature is continuously increased, an increase in pressure then follows within the exogenous glands (due to the expansion of the volatile compounds), leading to the cellular wall breakage and the release of the essential oil.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygenated compounds, such as 1,8‐cineole and camphor, which have a highly complex permittivity, can be extracted more easily due to their strong MW interaction. On the other hand, the hydrocarbon monoterpenes, such as α‐pinene and limonene, show less of an MW interaction, leading to a different release of the volatile compounds from exogenous secreting glands (washing and diffusion effects) . This possible mechanism is favoured since a high substrate/water ratio (1:5) was performed for both extraction approaches (MWHD and HD).…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic models play an important function for hydrodistillation processes under both technological and economic perspectives. Another study demonstrated the relationship between drying of the material to the performance and composition of essential oil [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%